Backwater device used on centrifugal pump - CHEN YUEWEI; ZHANG BINBIN; ZHANG LEI; ZHOU MAOQIAN; ZOU ZHONGFEI; TIAN LI (2017)
The invention discloses a backwater device used on a centrifugal pump. The backwater device comprises a centrifugal pump, a water sucking tube and a water outlet tube, wherein a check valve is arranged on the water sucking tube; a branch backwater tube is arranged between the water outlet tube and the water sucking tube; a valve is arranged on the branch backwater tube. Therefore, when a pump shell and the water sucking tube need to be filled with water at operation intervals, the valve can be opened, then water inside the water outlet tube can flow back into the pump shell and the water sucking tube, and compared with a conventional artificial filling mode, the backwater device has the advantages of being convenient to operate, small in workload, high in working efficiency and the like. 本发明公开了种用在离心泵上的回水装置，包括离心泵、吸水管和出水管，在吸水管上设置有止回阀，在出水管和吸水管之间设置分支回水管，在该分支回水管上设置有阀门；这样在间隙工作需要将泵壳和吸水管注满水时，可打开阀门使出水管内的水倒流灌注在泵壳和吸水管内，与现有人工灌注方式相比，本发明具有操作方便，节省人力，工作效率高等优点。